Hambatan dalam Penerapan Teknik Evaluasi Non Tes di SDN Pinang 5 Tangerang - Ina Magdalena; Dias Julianti Agustin; Khairunnisa Khairunnisa (Jurnal Halaqah, 2020)
The activity learns and teaching in the school, of course, involve evaluation activity, this activity does for measure how far student understands and know the learning done, until the teacher and school component finds out deficiency the learn system. Evaluation divided into 2 types, that is the test and the non-test. The test usually uses in school as the test, and non-test in the 2013 curriculum do to measure student attitude, through observation, questionnaire, and any more. Of course, there is the resistance in evaluation non-test, like teacher unpreparedness to do and make non-test instruments although students do not understand how to do this scoring. So we do this research to see how far the application of this evaluation in the school.